Pengedaran Narkoba Oleh Anak Dibawah Umur di Bandar Lampung - Raudatul Zanah; Yovita Silpiani; Zainudin Hasan (Publikasi Indonesia, 2023)
This research is aimed at (1) finding and analyzing what causes children to be used as drug dealers, and (2) knowing and analyzing the legal arrangements used. The method used in collecting data is by using the method of document study, observation and interviews. The results of the study stated that (1) the form of drug abuse in the city of Bandar Lampung which was committed by minors was caused by several factors including the condition of the surrounding area, conditions of family harmony and material factors. Then the form of narcotics abuse is a child as a user and a child as a drug seller. Then if a minor violates the law, the thing that must be done is to give sanctions so that the child can realize that what he has done is wrong and can lead to violations of the law. The involvement of minors in narcotics is punishable under the Narcotics Law” No. 35 of 2009” in this case minors are entitled to legal protection under the Criminal Code and Law” no. 11 of 2012”. Where a child will get leniency, which is returned to his parents or six months of work training at the Lampung Provincial Social service.